Morphometric analysis of the sacrum using statistical shape modelling. Issue 1 (2nd January 2022) - Pier, Trevor; Milligan, Kenneth; Wuthrich, Zachary; Carpenter, R. Dana; Ayers, Reed; Jesse, Mary; Kleck, Christopher; Patel, Vikas
ABSTRACT: Statistical shape modelling is a computational method that has been shown to be effective in describing variations in orthopaedic anatomy. Here, we present a statistical shape model of the sacrum and discuss how variations of this shape model compare to clinical observations. The shape model that we have created is successful in replicating clinically observed variations of the sacral side of the sacroiliac (SI) joint. Since previous research states that sacroiliac joint shape may be related to pain, this shape model could be effective in creating a shape dependent biomechanical model to study the underlying mechanism of shape and SI joint pain.